Exploring The Cultural Barrier of Indonesian Pre-Service English Teachers During Their Teaching Practice at Primary School in Thailand - Kuncahyo, Nanda Lintang Utari; Madjid, Hilda Izzati; Rakhmawati, Rakhmawati; Da-Oh, Maskah; Syaifudin, Mokhamad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Understanding cultural barriers is crucial in the context of increasing global collaboration in education. This research addresses a gap in the literature by focusing on the cultural barriers hindering the Indonesian pre-service English teacher’s learning process and the strategies to deal with it in a cross-cultural context which is in Thailand primary school. Through qualitative research, involving semi-structured interviews that allowed participants to share their unique challenges and perspectives, three types of cultural barriers are identified; 1) Communication barriers due to language differences, English knowledge and skills of the Thai students; 2) Knowledge about the education of the host country which involves unfamiliarity with the Thai curriculum and Thai primary school learning routines; 3) The integration of technology as there is no facilitate to integrate technology and students’ misbehaviour. Thus, nine types of strategies to overcome these cultural barriers employed include harnessing various tools, asking for help from local people, utilizing verbal and non-verbal language, employing instructional strategy, applying a social approach, planning lessons and units, grouping students for instruction, using verbal intervention, and resorting to logical consequence. These findings emphasize the importance of training for future educators to thrive in cross-cultural contexts, highlighting the need for further research in policy and program development for pre-abroad training of aspiring teachers.